Assessment of Foreign Body Aspiration Material Using a Virtual Bronchoscopy Model: Time-Density and Time-Volume Relationships - Tartar, Tugay; Bakal, Unal; Onur, Mehmet Ruhi; Sarac, Mehmet; Poyraz, Ahmet Kursad; Kazez, Ahmet (Kowsar Publ, 2017)
Background: During foreign body aspiration (FBA), identifying the type of object is frequently problematic. Objectives: This study assessed density changes over time in the most common organic, FBA materials using virtual bronchoscopy. We also examined volumetric changes in materials to determine the optimal removal time for each type of foreign body. Materials and Methods: Size-appropriate slots for each type of foreign body were created on a 2 x 30 x 30 cm sponge plate. Objects ( shelled and blanched peanuts, roasted chickpeas, hazelnuts, walnuts, almonds, pistachios, watermelon seeds, shelled and unshelled sunflower seeds, shelled and unshelled pumpkin seeds, chickpeas, beans, lemon seeds, and apple seeds) were placed into the slots, after which a second sponge, with identical dimensions, was placed over the top of the first sponge to achieve closure. A moist environment was maintained for 7 days at body temperature (37 degrees C). Multidetector computed tomography (MDCT) images of the sponges, volume and density measurements of objects performed each day were recorded. Intra-object differences in density and volume over time on MDCT were evaluated using time-density and time-volume curves, respectively. The SPSS for Windows software package (ver. 21.0; SPSS Inc., Chicago, IL, USA) was used to perform analyses. Pearson correlation analyses were used to determine differences in the volume and density of FBA materials across days. A time volumetric graph was also obtained. P < 0.05 was considered as significant. Results: Following aspiration, organic material volumes on day 7 were below baseline values, although objects exhibited a 30% average increase in volume during the first 4 days. The density values of objects increased between days 2 and 5, and decreased thereafter. Conclusions: Measuring daily changes in density allows for the identification of FBA materials. Our data indicate that object removal during days 1 - 3, and on day 7 should be easier compared to days 4 - 6.
Keywords: Foreign Body Aspiration; Virtual Bronchoscopy; Density; Volume